Modified slag sulfoaluminate cement-based ultra-high performance concrete and its preparation method
By using modified slag sulfaluminate cement-based materials in ultra-high performance concrete, combining nano alumina and rare earth polycarboxylic acid water reducing agents, the problems of high cement consumption and high energy consumption are solved, and low Ultra-high performance concrete with low carbon energy consumption improves early and late strength, and reduces hydration heat and self-shrinkage, which is suitable for the high strength and high toughness requirements of engineering structures.
Patent Information
- Application Number
- CN202411530614.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
During the manufacturing process, ultra-high performance concrete uses high cement, consumes a large amount of energy, and emits high CO2, resulting in high cost and does not comply with the carbon emission reduction policy, and has problems of high self-shrinkage and hydration heat, which limits its application and promotion. .
Modified slag sulfaaluminate cement-based ultra-high performance concrete, combined with nano alumina and rare earth polycarboxylic acid reduction by adding sulfaa cement, ordinary silicate cement, activated granulated blast furnace slag powder and angypsum Water agent and nano SiO2 combined with silane coupling agent modify polyformaldehyde fibers to form low-carbon and low-energy gelling materials, improve early and later strength, reduce hydration heat and self-contraction.
Ultra-high performance concrete with low hydration heat, low shrinkage, high early strength and stable later strength has been achieved, which significantly reduces cement usage, saves costs, improves the utilization rate of industrial solid waste of materials, and complies with the requirements of carbon emission reduction policies.
Smart Images

Figure CN119038943B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, and in particular to a modified slag sulphoaluminate cement-based ultra-high performance concrete and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete (UHPC) is a new type of cement-based engineering material with ultra-high strength and excellent durability. Today, the development and application of UHPC has become an important trend in the development of cement-based composite materials. However, the amount of cement required to manufacture UHPC is about three times that of ordinary concrete, which results in high material cost, high energy consumption, and high CO2 emissions of UHPC, which is not in line with the current carbon reduction policy.
[0003] The above problems restrict the further application and promotion of UHPC. Therefore, it is necessary to optimize the material composition to reduce cement consumption and overcome its shortcomings in engineering applications (such as high shrinkage and hydration heat, etc.). Summary of the invention
[0004] In view of the above problems, the present invention aims to provide a modified slag sulphoaluminate cement-based ultra-high performance concrete and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] On the one hand, a modified slag sulphoaluminate cement-based ultra-high performance concrete is provided, comprising the following raw material components in parts by weight: 36 to 108 parts of sulphoaluminate cement, 24 to 72 parts of ordinary Portland cement, 720 to 924 parts of activated granulated blast furnace slag powder, 216 to 300 parts of anhydrite, 1200 to 1320 parts of quartz sand, 12 to 36 parts of nano alumina, 9.6 to 24 parts of rare earth polycarboxylic acid water reducer, 13 to 28 parts of polyoxymethylene fiber modified by nano-SiO2 and silane coupling agent, and 192 to 240 parts of water.
[0007] Preferably, the activated granulated blast furnace slag powder is prepared by the following steps:
[0008] Add the granulated blast furnace slag powder to be activated into the carbonization stirring device, open the carbon dioxide ventilation valve of the carbonization stirring device, and set the temperature to 30 ℃ ~ 65 ℃, the humidity to 10% ~ 40%, the pressure to 1MPa ~ 2.5MPa, the time to 60 min ~ 150 min, and the carbon dioxide concentration to 20% ~ 99%;
[0009] The carbonization stirring device is started to continuously and evenly stir the granulated blast-furnace slag powder to be activated to carbonize it, thereby obtaining the activated granulated blast-furnace slag powder.
[0010] Preferably, the quartz sand is continuously graded in 20-40 mesh, 40-70 mesh, and 70-110 mesh, and the proportion of quartz sand of each mesh size is 2-5:3-5:3-5.
[0011] Preferably, the diameter of the nano-alumina is 20 nm to 100 nm.
[0012] Preferably, the rare earth polycarboxylate water reducer comprises lanthanum oxide and polycarboxylate water reducer, and the lanthanum oxide accounts for 5-15% of the total mass of the rare earth polycarboxylate water reducer, and the water reduction rate of the rare earth polycarboxylate water reducer is greater than 30%.
[0013] Preferably, the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is prepared by the following steps:
[0014] Firstly, the polyoxymethylene fiber is soaked in nitric acid with a concentration of 15% to 25%, and after soaking, it is rinsed with deionized water until the pH value of the rinse water reaches 7, and then dried to obtain the pretreated polyoxymethylene fiber;
[0015] Secondly, a surface treatment agent is prepared, wherein the surface treatment agent includes 1000 mL of anhydrous ethanol, 80 mL of ethyl orthosilicate, 0.5% to 2.5% by mass of a silane coupling agent, and 1% to 2% by mass of an ionic surfactant;
[0016] Then, the pretreated polyoxymethylene fiber is added to the surface treatment agent, and the amount of the pretreated polyoxymethylene fiber is 2% to 5% of the mass of the surface treatment agent, and the pH value is adjusted to alkaline conditions, ultrasonic dispersion is performed for 30 minutes, and the mixture is reacted in a constant temperature water bath at 25°C to 45°C for 6 hours to 12 hours, and then aged at room temperature for 24 hours;
[0017] Finally, the aged product is repeatedly washed with deionized water, and the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is obtained after drying.
[0018] Preferably, the silane coupling agent is any one of KH550, KH560, KH570 or KH792.
[0019] Preferably, the ionic surfactant is hexadecyltrimethylammonium bromide.
[0020] Preferably, the aspect ratio of the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is 60-67, the tensile strength is greater than or equal to 900 MPa, and the amount of nano-SiO2 attached is 10% to 15% of the fiber mass.
[0021] On the other hand, a method for preparing the modified slag sulphoaluminate cement-based ultra-high performance concrete according to any one of the above is also provided, comprising the following steps:
[0022] S1: adding sulphoaluminate cement, ordinary Portland cement, activated granulated blast furnace slag powder, anhydrite, nano alumina and rare earth polycarboxylate water reducer into a mixer, and stirring evenly to obtain a mixture 1;
[0023] S2: adding the quartz sand to the mixture 1 and stirring evenly to obtain a mixture 2;
[0024] S3: adding water in an amount greater than or equal to half of the amount to the mixture 2, stirring evenly, to obtain a mixture 3;
[0025] S4: adding the remaining amount of water to the mixture three, stirring evenly, to obtain a mixture four;
[0026] S5: adding the nano-SiO2 and silane coupling agent modified polyoxymethylene fiber to the mixture 4, stirring evenly, to obtain a mixture 5;
[0027] S6: pouring the mixture into a mold, vibrating it into shape, covering it with a plastic film after pouring, demolding it after 24 hours, and curing it in a curing room with a temperature of 20±2°C and a relative humidity of ≥95% to a specified age to obtain the modified slag sulphoaluminate cement-based ultra-high performance concrete.
[0028] The beneficial effects of the present invention are:
[0029] The present invention adds sulphoaluminate cement, ordinary Portland cement, activated granulated blast furnace slag powder and anhydrite, and can use high-activity sulphoaluminate cement to cooperate with gypsum to stimulate slag powder to form low-carbon and low-energy consumption slag sulphoaluminate cement, thereby improving the early strength and stable later strength of concrete and excellent durability; and the slag powder of the present invention adopts activated granulated blast furnace slag powder, which has a higher dissolution and hydration reaction rate, so that more ettringite and CSH gel are formed in the early stage, and the porosity is lower, which is conducive to the development of the early strength of the slag sulphoaluminate cement; so that it can exert higher strength The invention discloses a method for improving the workability of slag sulphoaluminate cement-based ultra-high performance concrete by using a rare earth polycarboxylate water-reducing agent, so as to ensure the workability of the slag sulphoaluminate cement-based ultra-high performance concrete mixture while increasing the strength and durability of the slag sulphoaluminate cement-based ultra-high performance concrete; the method comprises the steps of: using nano-SiO2 and a silane coupling agent to modify polyoxymethylene fiber, improving the bonding performance of the fiber interface, thereby strengthening and toughening the slag sulphoaluminate cement-based ultra-high performance concrete; in summary, the modified slag sulphoaluminate cement-based ultra-high performance concrete of the invention has the advantages of low hydration heat, low shrinkage, high early strength, stable late strength, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0031] Figure 1 It is a schematic diagram of the structure of a device for preparing activated granulated blast furnace slag powder in a specific embodiment;
[0032] Figure 2 The schematic diagram of the preparation process of polyoxymethylene fiber modified by nano-SiO2 and silane coupling agent in a specific embodiment;
[0033] Figure 3 This is a SEM image of polyoxymethylene fiber modified by nano-SiO2 and silane coupling agent in a specific embodiment;
[0034] Figure 4 The figure is a schematic diagram of the preparation process of modified slag sulphoaluminate cement-based ultra-high performance concrete in a specific embodiment. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0036] On the one hand, the present invention provides a modified slag sulphoaluminate cement-based ultra-high performance concrete, comprising the following raw material components in parts by weight: 36 to 108 parts of sulphoaluminate cement, 24 to 72 parts of ordinary Portland cement, 720 to 924 parts of activated granulated blast furnace slag powder, 216 to 300 parts of anhydrite, 1200 to 1320 parts of quartz sand, 12 to 36 parts of nano alumina, 9.6 to 24 parts of rare earth polycarboxylate water reducer, 13 to 28 parts of polyoxymethylene fiber modified by nano-SiO2 and silane coupling agent, and 192 to 240 parts of water.
[0037] The present invention uses a small amount of highly active sulphoaluminate cement and ordinary silicate cement to cooperate with gypsum to activate granulated blast furnace slag powder, and the low-carbon and low-energy consumption sulphoaluminate cement formed as the cementing material to prepare the slag sulphoaluminate cement-based ultra-high performance concrete, whose industrial solid waste content is as high as 85-95wt.%, which can absorb a large amount of industrial solid waste such as slag and industrial by-product gypsum, greatly reducing the amount of cement and other cementing materials, which saves a lot of costs while ensuring the workability and mechanical properties of ultra-high performance concrete, and is of great significance to social energy conservation and ecological environmental protection. At the same time, nano-alumina is added to the system, which is attached to the surface of particles such as mineral powder and cement or filled in the pores between the particles of the cementing material, providing nucleation sites for hydration products and participating in the hydration reaction to generate more AFt, CSH and CASH, thereby improving the early compressive strength of the slag sulphoaluminate cement-based ultra-high performance concrete and reducing pores.
[0038] The use of activated granulated blast furnace slag powder can not only accelerate the breaking of the Ca-O bond in the slag, forming a large number of dangling chemical bonds and increasing the activity, but also contribute to the formation of active calcium carbonate, amorphous SiO2 and C-(A)-SH gel. These products can accelerate the reaction in the cementitious material due to the "nucleus effect" and increase the density of the matrix structure.
[0039] The use of nano-SiO2 combined with silane coupling agent to modify polyformaldehyde fiber can effectively solve the problems of poor wettability and adhesion between the polyformaldehyde fiber matrix and inability to effectively transfer external loads. The nano-SiO2 on the surface of polyformaldehyde fiber can serve as a nucleation site for cement hydration products, increase the roughness of the fiber surface, and enhance the mechanical bite of the interface. At the same time, it can react with CH to generate CSH gel to fill the weak area of the interface. The silane coupling agent used can simultaneously connect with the polyformaldehyde fiber and the inorganic matrix through its own multi-functional groups, and form a "bridge" between the polyformaldehyde fiber and the inorganic matrix through physical and chemical effects, or improve the interface material morphology between the fiber and the matrix, thereby enhancing the bonding strength between the fiber and the matrix and improving the mechanical properties and durability of the composite material.
[0040] The present invention adds a rare earth polycarboxylate water reducer into the system, which can effectively change the interfacial energy of cement and mineral powder hydration products by utilizing the rare earth components therein while playing a role of high-efficiency water reduction, and can refine the grain structure of the cement and mineral powder hydration products and improve the shape of crystal dendrites, so that the slag sulphoaluminate cement-based ultra-high performance concrete is more compact in microstructure, and the strength is significantly increased in macroscopic, and the fluidity is also improved.
[0041] In a specific embodiment, the activated granulated blast furnace slag powder is prepared by the following steps:
[0042] Add the granulated blast furnace slag powder to be activated into the carbonization stirring device, open the carbon dioxide ventilation valve of the carbonization stirring device, and set the temperature to 30 ℃ ~ 65 ℃, the humidity to 10% ~ 40%, the pressure to 1MPa ~ 2.5MPa, the time to 60 min ~ 150 min, and the carbon dioxide concentration to 20% ~ 99%;
[0043] The carbonization stirring device is started to continuously and evenly stir the granulated blast-furnace slag powder to be activated to carbonize it, thereby obtaining the activated granulated blast-furnace slag powder.
[0044] In the above embodiments, the present invention achieves rapid and sufficient carbonization of the ore powder under pressure by accurately controlling the temperature, humidity, time, pressure and carbon dioxide concentration, further improves the activity of the granulated blast furnace slag powder, solves the problem of low activity of the ore powder, realizes the effective utilization of secondary resources, and can effectively absorb and solidify CO2 gas. In a specific embodiment, the carbon fixation amount of the activated granulated blast furnace slag powder after activation is 5% to 30%, and the density is increased by 1% to 20%.
[0045] In a specific embodiment, the quartz sand is continuously graded in 20-40 mesh, 40-70 mesh, and 70-110 mesh, and the proportion of quartz sand of each mesh is 2-5:3-5:3-5; the diameter of the nano-alumina is 20 nm-100 nm.
[0046] In a specific embodiment, the rare earth polycarboxylate water reducer comprises lanthanum oxide and polycarboxylate water reducer, and the lanthanum oxide accounts for 5-15% of the total mass of the rare earth polycarboxylate water reducer, and the water reduction rate of the rare earth polycarboxylate water reducer is greater than 30%.
[0047] In a specific embodiment, the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is prepared by the following steps:
[0048] Firstly, the polyoxymethylene fiber is soaked in nitric acid with a concentration of 15% to 25%, and after soaking, it is rinsed with deionized water until the pH value of the rinse water reaches 7, and then dried to obtain the pretreated polyoxymethylene fiber;
[0049] Secondly, a surface treatment agent is prepared, wherein the surface treatment agent includes 1000 mL of anhydrous ethanol, 80 mL of ethyl orthosilicate, 0.5% to 2.5% by mass of a silane coupling agent, and 1% to 2% by mass of an ionic surfactant;
[0050] Then, the pretreated polyoxymethylene fiber is added to the surface treatment agent, and the amount of the pretreated polyoxymethylene fiber is 2% to 5% of the mass of the surface treatment agent, and the pH value is adjusted to alkaline conditions, ultrasonic dispersion is performed for 30 minutes, and the mixture is reacted in a constant temperature water bath at 25°C to 45°C for 6 hours to 12 hours, and then aged at room temperature for 24 hours;
[0051] Finally, the aged product is repeatedly washed with deionized water, and the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is obtained after drying.
[0052] In the above embodiment, the present invention modifies the polyformaldehyde fiber by combining nano-SiO2 with a silane coupling agent. Compared with the single traditional fiber surface modification technology, the modification method of nano-SiO2 combined with a silane coupling agent has a simple process, uniform coating thickness and a smooth surface, and can solve the problems of weak bonding between polyformaldehyde fiber and substrate, and easy agglomeration of fiber and nano-SiO2. At the same time, the silane coupling agent can also improve the corrosion resistance of the fiber and the specimen.
[0053] In a specific embodiment, the silane coupling agent is any one of KH550, KH560, KH570 or KH792; and the ionic surfactant is hexadecyltrimethylammonium bromide.
[0054] In a specific embodiment, the aspect ratio of the polyoxymethylene fiber modified by nano-SiO2 and silane coupling agent is 60-67, the tensile strength is greater than or equal to 900 MPa, and the amount of nano-SiO2 attached is 10% to 15% of the fiber mass.
[0055] On the other hand, the present invention also provides a method for preparing the modified slag sulphoaluminate cement-based ultra-high performance concrete as described in any one of the above, comprising the following steps:
[0056] S1: adding sulphoaluminate cement, ordinary Portland cement, activated granulated blast furnace slag powder, anhydrite, nano alumina and rare earth polycarboxylate water reducer into a mixer, and stirring evenly to obtain a mixture 1;
[0057] S2: adding the quartz sand to the mixture 1 and stirring evenly to obtain a mixture 2;
[0058] S3: adding water in an amount greater than or equal to half of the amount to the mixture 2, stirring evenly, to obtain a mixture 3;
[0059] S4: adding the remaining amount of water to the mixture three, stirring evenly, to obtain a mixture four;
[0060] S5: adding the nano-SiO2 and silane coupling agent modified polyoxymethylene fiber to the mixture 4, stirring evenly, to obtain a mixture 5;
[0061] S6: pouring the mixture into a mold, vibrating it into shape, covering it with a plastic film after pouring, demolding it after 24 hours, and curing it in a curing room with a temperature of 20±2°C and a relative humidity of ≥95% to a specified age to obtain the modified slag sulphoaluminate cement-based ultra-high performance concrete.
[0062] Example 1
[0063] A modified slag sulphoaluminate cement-based ultra-high performance concrete comprises the following raw material components in parts by weight: 36 parts of sulphoaluminate cement, 24 parts of ordinary Portland cement, 900 parts of activated granulated blast furnace slag powder, 240 parts of anhydrite, 1200 parts of quartz sand, 24 parts of nano alumina, 12 parts of rare earth polycarboxylate water reducer, 13 parts of polyoxymethylene fiber modified by nano-SiO2 and silane coupling agent, and 216 parts of water.
[0064] Example 2
[0065] A modified slag sulphoaluminate cement-based ultra-high performance concrete comprises the following raw material components in parts by weight: 84 parts of sulphoaluminate cement, 48 parts of ordinary Portland cement, 852 parts of activated granulated blast furnace slag powder, 216 parts of anhydrite, 1200 parts of quartz sand, 24 parts of nano-alumina, 12 parts of rare earth polycarboxylate water reducer, 13 parts of polyoxymethylene fiber modified by nano-SiO2 and silane coupling agent, and 216 parts of water.
[0066] Example 3
[0067] A modified slag sulphoaluminate cement-based ultra-high performance concrete comprises the following raw material components in parts by weight: 108 parts of sulphoaluminate cement, 72 parts of ordinary Portland cement, 720 parts of activated granulated blast furnace slag powder, 300 parts of anhydrite, 1200 parts of quartz sand, 24 parts of nano-alumina, 12 parts of rare earth polycarboxylate water reducer, 13 parts of polyoxymethylene fiber modified by nano-SiO2 and silane coupling agent, and 216 parts of water.
[0068] In the above-mentioned Examples 1 to 3, the sulphoaluminate cement is 42.5 grade high belite sulphoaluminate cement; the ordinary Portland cement is PO52.5 grade ordinary Portland cement; the activated granulated blast furnace slag powder complies with the provisions of GB / T 203 and GB / T 18046-2017 S105 grade, and the carbon fixation is 20%, and the density is increased by 15%; the anhydrite is natural anhydrite, wherein the sulfur trioxide content is greater than 47wt.%; the quartz sand is a continuous graded quartz sand of 20-40 mesh, 40-70 mesh, and 70-110 mesh in a proportion of 3:4:3; the diameter of the nano alumina is 20nm-100nm; the rare earth polycarboxylate water reducer is a powder, wherein the lanthanum oxide content is 10wt.%, and the water reduction rate is 32%; the aspect ratio of the nano SiO2 combined with the silane coupling agent modified polyoxymethylene fiber is 60, and the tensile strength is 998 MPa, and the amount of nano-SiO2 attached is about 12% of the fiber mass.
[0069] like Figure 1 As shown, the activated granulated blast furnace slag is prepared by the following steps: adding the granulated blast furnace slag powder to be activated into a carbonization stirring device, opening the carbon dioxide ventilation valve of the carbonization stirring device, and setting the temperature to 60°C, the humidity to 40%, the pressure to 2.1 MPa, the time to 150 min, and the carbon dioxide concentration to 20%; starting the carbonization stirring device, continuously and uniformly stirring the granulated blast furnace slag powder to be activated to carbonize it, and obtaining the activated granulated blast furnace slag powder.
[0070] like Figure 2 As shown, the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is prepared by the following steps:
[0071] Firstly, the polyoxymethylene fiber was soaked in 20% nitric acid to carry out liquid phase oxidation treatment and remove grease and impurities on the surface. After soaking, it was rinsed with deionized water until the pH value of the rinse water reached 7, and then dried at 50 ℃ for 12 h to obtain the pretreated polyoxymethylene fiber.
[0072] Secondly, a surface treatment agent is prepared, wherein the surface treatment agent includes 1000 mL of anhydrous ethanol, 80 mL of tetraethyl orthosilicate, 1.5% by mass of a silane coupling agent KH550, and 1% by mass of an ionic surfactant hexadecyltrimethylammonium bromide (CTAB);
[0073] Then, 13 g of the pretreated polyoxymethylene fiber was added to the surface treatment agent, and 40 mL of concentrated ammonia water was added to provide alkaline conditions to induce catalytic reaction. After that, it was covered with plastic wrap to prevent ammonia volatilization. Ultrasonic dispersion was performed for 30 min, and the reaction was carried out in a constant temperature water bath at 45 ° C for 12 h, and then aged at room temperature for 24 h;
[0074] Finally, the aged product was repeatedly washed with deionized water and dried at 50 °C for 12 h to obtain the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber, the SEM image of which is shown in FIG. Figure 3 shown.
[0075] like Figure 4 As shown, the modified slag sulphoaluminate cement-based ultra-high performance concrete is prepared by the following steps:
[0076] (1) adding sulphoaluminate cement, ordinary Portland cement, activated granulated blast furnace slag powder, anhydrite, nano alumina and rare earth polycarboxylate water reducer into a mixer, stirring evenly to obtain a mixture 1;
[0077] (2) adding the quartz sand to the mixture 1 and stirring evenly to obtain the mixture 2;
[0078] (3) adding 75 wt.% of water to the mixture 2 and stirring evenly to obtain a mixture 3;
[0079] (4) adding the remaining 25 wt.% of water to the mixture (3) and stirring evenly to obtain a mixture (4);
[0080] (5) adding the nano-SiO2 and silane coupling agent modified polyoxymethylene fiber to the mixture 4, stirring evenly, to obtain a mixture 5;
[0081] (6) pouring the mixture into a mold, vibrating it into shape, covering it with a plastic film after pouring, demolding it after 24 hours, and curing it in a curing room at a temperature of 20±2°C and a relative humidity of ≥95% to a specified age, thereby obtaining the modified slag sulphoaluminate cement-based ultra-high performance concrete.
[0082] Comparative Example 1
[0083] Different from Example 1, the slag powder in this comparative example is granulated blast furnace slag powder that has not been activated, and the granulated blast furnace slag powder that has not been activated complies with GB / T 203 and complies with the provisions of S95 or S105 in GB / T 18046-2017.
[0084] Comparative Example 2
[0085] Different from Example 2, the water reducer in this comparative example is a common polycarboxylate water reducer (Swiss Sika 540P, with a water reduction rate of 30%), that is, the water reducer does not contain the lanthanum oxide.
[0086] Comparative Example 3
[0087] Different from Example 2, the water reducing agent used in this comparative example is calcium lignin sulfonate water reducing agent (water reduction rate is 12%).
[0088] Comparative Example 4
[0089] Different from Example 2, the water reducing agent in this comparative example is UNF-5 naphthalene-based water reducing agent (water reduction rate is 21.8%).
[0090] Comparative Example 5
[0091] Different from Example 3, the fiber in this comparative example is polyoxymethylene fiber (with an aspect ratio of 60 and a tensile strength of 1087 MPa) that has not been modified with nano-SiO2 and silane coupling agent.
[0092] Comparative Example 6
[0093] Different from Example 3, the fiber in this comparative example is polyethylene fiber modified by nano-SiO2 and silane coupling agent (with an aspect ratio of 308 and a tensile strength of 1564 MPa (the tensile strength of the unmodified polyethylene fiber is 1620 MPa)).
[0094] Comparative Example 7
[0095] Different from Example 3, the fiber in this comparative example is ramie fiber modified by nano-SiO2 and silane coupling agent (with an aspect ratio of 700 and a tensile strength of 468 MPa (the tensile strength of ramie fiber before modification is 500 MPa)).
[0096] Comparative Example 8
[0097] Different from Example 3, the slag powder in this comparative example is granulated blast furnace slag powder that has not been activated, and the granulated blast furnace slag powder that has not been activated complies with GB / T 203 and complies with the provisions of S95 or S105 in GB / T 18046-2017; the water reducer in this comparative example is ordinary polycarboxylate water reducer (Swiss Sika 540P, with a water reduction rate of 30%), that is, the water reducer does not contain the lanthanum oxide; the fiber in this comparative example is polyoxymethylene fiber (aspect ratio of 60, tensile strength of 1087 MPa) that has not been modified with nano-SiO2 and silane coupling agent.
[0098] Test Example 1
[0099] The concrete prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 8 was tested for fluidity, flexural strength and compressive strength; the fluidity determination method was based on GB / T 2419-2005, and the flexural strength and compressive strength test procedures were based on GB / T 17671-2021; the test results are shown in Table 1:
[0100] Table 1 Test results of concrete fluidity and strength of each embodiment and each comparative example
[0101]
[0102] From Table 1 we can see that:
[0103] The modified slag sulphoaluminate cement-based ultra-high performance concrete prepared in Example 1 of the present invention has significantly improved early and late flexural strength and compressive strength compared to the concrete in Comparative Example 1. This indicates that the activated granulated blast furnace slag powder of the present invention can effectively improve the activity of granulated blast furnace slag powder, promote the disintegration of the main component granulated blast furnace slag powder, make its hydration reaction more complete, and effectively improve the mechanical properties of slag sulphoaluminate cement-based ultra-high performance concrete.
[0104] The modified slag sulphoaluminate cement-based ultra-high performance concrete prepared in Example 2 of the present invention has significantly improved fluidity, flexural strength and compressive strength compared to the concrete of Comparative Examples 2 to 4, indicating that the rare earth polycarboxylate water reducer used in the present invention is more suitable for this system than ordinary polycarboxylate water reducers, calcium lignin sulfonate water reducers and UNF-5 naphthalene water reducers, and the effect of improving fluidity is more obvious. At the same time, its rare earth component lanthanum oxide also plays a role in refining the grain structure of the hydration products of cement and mineral powder, making the microstructure of the slag sulphoaluminate cement-based ultra-high performance concrete more compact, thereby improving the flexural strength and compressive strength.
[0105] The modified slag sulphoaluminate cement-based ultra-high performance concrete prepared in Example 3 of the present invention has significantly improved flexural strength compared to the concrete of Comparative Examples 5 to 7, indicating that compared to unmodified polyoxymethylene fiber, polyethylene fiber modified by nano-SiO2 combined with silane coupling agent, and ramie fiber modified by nano-SiO2 combined with silane coupling agent, the polyoxymethylene fiber modified by nano-SiO2 combined with silane coupling agent has more obvious reinforcing and toughening effects, and has less impact on fluidity. Compared to the concrete of Comparative Example 8, the modified slag sulphoaluminate cement-based ultra-high performance concrete after optimization of the present invention has significantly improved fluidity, flexural strength and compressive strength, and has better performance.
[0106] Test Example 2
[0107] The concretes prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were tested for setting time according to GB / T 1346-2011 "Test Methods for Water Consumption, Setting Time and Stability of Cement Standard Consistency". The test results are shown in Table 2:
[0108] Table 2 Test results of setting time of concrete in various embodiments and comparative examples
[0109]
[0110] From Table 2 we can see that:
[0111] The modified slag sulphoaluminate cement-based ultra-high performance concrete prepared in Example 1 of the present invention has an initial setting time shortened by about 38% and a final setting time shortened by about 34% compared with the concrete in Comparative Example 1. This indicates that the activated granulated blast furnace slag powder of the present invention effectively improves the activity of the granulated blast furnace slag powder, accelerates the slag dissolution rate and the hydration reaction rate, and effectively shortens the initial setting and final setting times.
[0112] The modified slag sulphoaluminate cement-based ultra-high performance concrete prepared in Example 2 of the present invention has significantly shorter initial setting time and final setting time than the concrete of Comparative Examples 2 to 4, indicating that the rare earth polycarboxylate water reducer used in the present invention not only plays a role in reducing water, but also further promotes the hydration of cement and mineral powder, accelerates the hydration process, generates more AFt and CSH gels, and thus greatly shortens the setting time. It also shows that ordinary polycarboxylate water reducer (540P) is not conducive to shortening the setting time of slag sulphoaluminate cement-based ultra-high performance concrete, and the lignin calcium sulfonate water reducer and UNF-5 naphthalene water reducer have poor compatibility with this system.
[0113] The modified slag sulphoaluminate cement-based ultra-high performance concrete prepared in Example 3 of the present invention has shorter initial setting and final setting times than the concrete of Comparative Examples 6 and 7. Compared with the concrete of Comparative Example 8, the modified slag sulphoaluminate cement-based ultra-high performance concrete prepared in the present invention has significantly shorter setting time, which solves the problems of low early strength and easy sanding caused by the slow hydration and hardening speed of slag sulphoaluminate cement.
[0114] In summary, the modified slag sulphoaluminate cement-based ultra-high performance concrete prepared by the present invention can achieve a flexural strength of 22.9 MPa, a compressive strength of 125.1 MPa, and a fluidity of 285 mm. The flexural strength, compressive strength, and fluidity are greatly improved on the basis of unmodified slag sulphoaluminate cement-based ultra-high performance concrete and ordinary slag sulphoaluminate cement, which greatly expands the application range of slag sulphoaluminate cement-based ultra-high performance concrete and can meet the material requirements of engineering structures that require high strength, high toughness, and high durability.
[0115] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical contents to make some changes or modifications to the embodiments are equivalent embodiments of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A modified slag sulphoaluminate cement-based ultra-high performance concrete, characterized in that: The invention comprises the following raw material components in parts by weight: 36-108 parts of sulphoaluminate cement, 24-72 parts of ordinary silicate cement, 720-924 parts of activated granulated blast furnace slag powder, 216-300 parts of anhydrite, 1200-1320 parts of quartz sand, 12-36 parts of nano-alumina, 9.6-24 parts of rare earth polycarboxylate water reducer, 13-28 parts of nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber, and 192-240 parts of water; The activated granulated blast furnace slag powder is prepared by the following steps: Add the granulated blast furnace slag powder to be activated into the carbonization stirring device, open the carbon dioxide ventilation valve of the carbonization stirring device, and set the temperature to 30 ℃ ~ 65 ℃, the humidity to 10% ~ 40%, the pressure to 1 MPa ~ 2.5 MPa, the time to 60 min ~ 150 min, and the carbon dioxide concentration to 20% ~ 99%; Starting the carbonization stirring device to continuously and uniformly stir the granulated blast-furnace slag powder to be activated to carbonize it, thereby obtaining the activated granulated blast-furnace slag powder; The nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is prepared by the following steps: Firstly, the polyoxymethylene fiber is soaked in nitric acid with a concentration of 15% to 25%, and after soaking, it is rinsed with deionized water until the pH value of the rinse water reaches 7, and then dried to obtain the pretreated polyoxymethylene fiber; Secondly, a surface treatment agent is prepared, wherein the surface treatment agent includes 1000 mL of anhydrous ethanol, 80 mL of ethyl orthosilicate, 0.5% to 2.5% by mass of a silane coupling agent, and 1% to 2% by mass of an ionic surfactant; Then, the pretreated polyoxymethylene fiber is added to the surface treatment agent, and the amount of the pretreated polyoxymethylene fiber is 2% to 5% of the mass of the surface treatment agent, and the pH value is adjusted to alkaline conditions, ultrasonic dispersion is performed for 30 minutes, and the mixture is reacted in a constant temperature water bath at 25°C to 45°C for 6 hours to 12 hours, and then aged at room temperature for 24 hours; Finally, the aged product is repeatedly washed with deionized water, and the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is obtained after drying.
2. The modified slag sulphoaluminate cement-based ultra-high performance concrete according to claim 1, characterized in that: The quartz sand is continuously graded in 20-40 meshes, 40-70 meshes, and 70-110 meshes, and the proportion of quartz sand of each mesh number is 2-5:3-5:3-5.
3. The modified slag sulphoaluminate cement-based ultra-high performance concrete according to claim 1, characterized in that: The diameter of the nano-aluminum oxide is 20 nm to 100 nm.
4. The modified slag sulphoaluminate cement-based ultra-high performance concrete according to claim 1, characterized in that: The rare earth polycarboxylate water reducer comprises lanthanum oxide and polycarboxylate water reducer, and the lanthanum oxide accounts for 5-15% of the total mass of the rare earth polycarboxylate water reducer, and the water reduction rate of the rare earth polycarboxylate water reducer is greater than 30%.
5. The modified slag sulphoaluminate cement-based ultra-high performance concrete according to claim 1, characterized in that: The silane coupling agent is any one of KH550, KH560, KH570 or KH792.
6. The modified slag sulphoaluminate cement-based ultra-high performance concrete according to claim 1, characterized in that: The ionic surfactant is hexadecyltrimethylammonium bromide.
7. The modified slag sulphoaluminate cement-based ultra-high performance concrete according to claim 1, characterized in that: The aspect ratio of the nano-SiO2 combined with silane coupling agent modified polyoxymethylene fiber is 60-67, the tensile strength is greater than or equal to 900 MPa, and the amount of nano-SiO2 attached is 10%-15% of the fiber mass.
8. The method for preparing modified slag sulphoaluminate cement-based ultra-high performance concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: adding sulphoaluminate cement, ordinary Portland cement, activated granulated blast furnace slag powder, anhydrite, nano alumina and rare earth polycarboxylate water reducer into a mixer, and stirring evenly to obtain a mixture 1; S2: adding the quartz sand to the mixture 1 and stirring evenly to obtain a mixture 2; S3: adding water in an amount greater than or equal to half of the amount to the mixture 2, stirring evenly, to obtain a mixture 3; S4: adding the remaining amount of water to the mixture 3, stirring evenly, to obtain a mixture 4; S5: adding the nano-SiO2 and silane coupling agent modified polyoxymethylene fiber to the mixture 4, stirring evenly, to obtain a mixture 5; S6: pouring the mixture into a mold, vibrating it into shape, covering it with a plastic film after pouring, demolding it after 24 hours, and curing it in a curing room with a temperature of 20±2°C and a relative humidity of ≥95% to a specified age to obtain the modified slag sulphoaluminate cement-based ultra-high performance concrete.
Citation Information
Patent Citations
Water reducing agent for rare earth concrete and preparation method
CN101050082A
Marine sulphoaluminate cement for rapid construction and preparation method thereof
CN110642579A
Cited By
Waterproof and anti-seepage high-strength concrete and preparation method thereof
CN121470842A